Single-shot spatiotemporal intensity measurement of picosecond laser pulses with compressed ultrafast photography. (May 2019) - Cao, Fengyan; Yang, Chengshuai; Qi, Dalong; Yao, Jiali; He, Yilin; Wang, Xing; Wen, Wenlong; Tian, Jinshou; Jia, Tianqing; Sun, Zhenrong; Zhang, Shian
Highlights: We developed an advanced compressed ultrafast photography technique to measure the spatiotemporal intensity distribution of the picosecond laser pulses, involving the experimental measurement system and the three-dimensional image reconstruction algorithm. Our compressed ultrafast photography system can measure the picosecond laser pulses with a wide spectral range from ultraviolet (200 nm) to near infrared (850 nm), which depends on the spectral response of the streak camera. Our compressed ultrafast photography system can measure the arbitrary spatiotemporal intensity distribution of the laser pulses within the temporal resolution of the streak camera (4 ps). The compressed ultrafast photography technique has the remarkable advantages with the single shot measurement and without the reference laser pulse. The compressed ultrafast photography technique extends the measurement of the picosecond laser pulses based on the streak camera from one dimension to two dimension in the space. Abstract: The spatiotemporal measurement of the ultrashort laser pulses is of great significance in the diagnosis of the instrument performance and the exploration of the laser and matter interaction. In this work, we report an advanced compressed ultrafast photography (CUP) technique to measure the spatiotemporal intensity distribution of the picosecond laser pulses with a single shot. This CUP technique is based on a three-dimensional image reconstruction strategy by employing the random codes to encode the space-time-evolving laser pulse and decode it based on a compressed sensing (CS) algorithm. In our CUP system, the measurable laser wavelength depends on the spectral response of the streak camera, which can cover a wide range from ultraviolet (200 nm) to near infrared (850 nm). Based on the CUP system we develop, we successfully measure the spatiotemporal intensity evolutions of some typical laser pulses, such as the 800 nm picosecond laser pulse, the 800 and 400 nm two-color picosecond laser pulses and the supercontinuum picosecond laser pulse. These experimental results show that the CUP technique can well characterize the spatiotemporal intensity information of the picosecond laser pulses. Moreover, this technique has the remarkable advantages with the single shot measurement and without the reference laser pulse.